Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Konsumen pada PT. Samudera Mandiri Sentosa Bitung - Devie Mathilda Lumentut; Silfia Karlina Walo (Global Leadership Organizational Research in Management, 2024)
The influence of product quality and brand image on consumer purchasing decisions at PT. Samudera Mandiri Sentosa Bitung. Department of Business Administration Dua Sudara Bitung College of Business and Management Bitung 2024. Problems regarding the influence of product quality and brand image on purchasing decisions at PT. Samudra Mandiri Sentosa in Bitung City. This research aims to see the influence. The population of this research is all consumers of PT. Samudera Mandiri Sentosa and samples were taken from 50 consumers. This research is quantitative research. This research data uses a questionnaire which is calculated using prerequisite tests and statistical tests. The results of this research concluded: there is an influence on product quality, brand image and consumer purchasing decisions.